Impact of global cooling on Early Cretaceous high pCO2 - L. Cavalheiro; T. Wagner; S. Steinig; C. Bottini; W. Dummann; O. Esegbue; G. Gambacorta; V. Giraldo-Gómez; A. Farnsworth; S. Flögel; P. Hofmann; D. J. Lunt; et al. (Nature Communications, 2021)
The Weissert Event similar to 133 million years ago marked a profound global cooling that punctuated the Early Cretaceous greenhouse. We present modelling, high-resolution bulk organic carbon isotopes and chronostratigraphically calibrated sea surface temperature (SSTs) based on an organic paleothermometer (the TEX86 proxy), which capture the Weissert Event in the semi-enclosed Weddell Sea basin, offshore Antarctica (paleolatitude similar to 54 degrees S; paleowater depth similar to 500 meters). We document a similar to 3-4 degrees C drop in SST coinciding with the Weissert cold end, and converge the Weddell Sea data, climate simulations and available worldwide multi-proxy based temperature data towards one unifying solution providing a best-fit between all lines of evidence. The outcome confirms a 3.0 degrees C (+/- 1.7 degrees C) global mean surface cooling across the Weissert Event, which translates into a similar to 40% drop in atmospheric pCO(2) over a period of similar to 700 thousand years. Consistent with geologic evidence, this pCO(2) drop favoured the potential build-up of local polar ice.